Risk–Benefit Assessment of Consumption of Rice for Adult Men in China - Fang, Haiqin; Zhang, Quantao; Zhang, Shengjie; Zhang, Tongwei; Pan, Feng; Cui, Yufeng; Thomsen, Sofie Theresa; Jakobsen, Lea S.; Liu, Aidong; Pires, Sara M. (Frontiers in Nutrition, 2021)
Objective: To evaluate the health impact of current and alternative patterns of rice consumption in Chinese adult men (40-79 years of age). Methods: We applied a risk-benefit assessment model that took into account the health effects of selenium (Se), cadmium (Cd) and inorganic arsenic (i-As). The health effects included prevention of prostate cancer associated with exposure to Se, and increased risk of lung, bladder and skin cancer for i-As and chronic kidney disease for Cd. We defined the baseline scenario as the current individual mean daily consumption of rice in the population of interest, and two alternative scenarios (AS): AS1=50 g/day, AS2=200 g/day. We estimated the health impact for different age groups in terms of change in Disability-Adjusted Life Years (∆DALY). Results: The baseline scenario of rice consumption was 71.5-105.4 g/day in different age groups of adult men in China. We estimated that for AS1, the mean ∆DALY was -2.76 - 46.2/100,000 adult men of 40-79 years old. For AS2, the ∆DALY was -112.0-95.5/100,000 individuals in this population group. Conclusion: Our results showed that, based on associated exposure to selenium, cadmium, and i-As in rice, the current consumption of rice does not pose a risk to adult men in China. Also, a lower (50 g / day) rice consumption will not bring larger beneficial effects, but a higher (200 g / day) rice consumption may increase the risk in the population between 40 and 69 years old, and increase the benefit in older men (≥ 70 years）.